(untitled) - Chance, Don M. (Mason, OH., 2008)
This book provides an outstanding blend of institutional material, theory, and practical applications with updates that reflect the most recent changes in today's financial world. You'll find detailed coverage of options, futures, forwards, swaps, and risk management as well as a balanced introduction to pricing, trading, and strategy. A variety of practical applications, memorable real business examples from real businesses, and minimal use of technical mathematics keep the text's presentation accessible.
Keywords: Derivative securities,Risk management.,Options ( Finance ),Futures market.,Quản lý rủi ro,Những tùy chọn ( Tài chính ),Thị trường kỳ hạn; Phát sinh an toàn